‘It's the little things that count’: healthcare professionals’ views on delivering dignified care: a qualitative study - Williams, V; Kinnear, D; Victor, C (Wiley, 2016)
Aims To explore healthcare professionals’ perspectives of dignified care and experiences of providing care.